Perilaku Masyarakat Memelihara Lingkungan pada Kompleks Perumahan Tipe Besar di Kabupaten Soppeng - Rahmansah, Rahmansah; Agustang, Andi; Pertiwi, Nurlita (Jurnal Ilmiah Mandala Education (JIME), 2022)
The purpose of this study was to determine: (1) the knowledge, attitudes, motivation, and behavior of the community in maintaining the housing environment in a large-type housing complex in Soppeng Regency, (2) the influence of knowledge, attitudes, and motivation individually and collectively on the behavior of the community in maintaining the housing environment in a large-type housing complex in Soppeng Regency. This type of research is correlational research located at a large type of housing complex in Soppeng Regency. The research sample were 50 heads of families selected by systimatic random sampling method. The variables considered were: knowledge, attitudes, motivation, and behavior in maintaining the housing environment. The analysis used were descriptive statistical analysis and inferential statistical analysis. The inferential models used are simple regression and multiple regression. The conclusions of the study are: (1) knowledge, attitudes, motivation, and behavior in maintaining the housing environment of the people who inhabit large type houses in Soppeng Regency are in the medium category, (2) knowledge, attitudes, and motivation have a significant effect individually and collectively together on the behavior of the community maintain a residential environment in a large-type housing complex in Soppeng Regency.